2015
DOI: 10.1051/0004-6361/201424769
|View full text |Cite
|
Sign up to set email alerts
|

Coronae of stars with supersolar elemental abundances

Abstract: Coronal elemental abundances are known to deviate from the photospheric values of their parent star, with the degree of deviation depending on the first ionization potential (FIP). This study focuses on the coronal composition of stars with supersolar photospheric abundances. We present the coronal abundances of six such stars: 11 LMi, ι Hor, HR 7291, τ Boo, and α Cen A and B. These stars all have high-statistics X-ray spectra, three of which are presented for the first time. The abundances we measured were ob… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 43 publications
0
5
2
Order By: Relevance
“…The comparison we make with the photosphere of ι Hor shows no trend related to the FIP. Our results differ from those of Peretz et al (2015) Peretz et al (2015) could be due to our better statistics, which allow us to use a 3-T model to fit the spectrum, thus with a better sampling of the region where oxygen lines are formed. Our result also contradicts the conclusion made by Wood & Linsky (2010), followed by Laming (2015), in which FIP-related effects in dwarfs are correlated with spectral type, using only stars with log L X (erg s −1 )< 29.…”
Section: ι Hor As a Young Solar Analogcontrasting
confidence: 80%
See 1 more Smart Citation
“…The comparison we make with the photosphere of ι Hor shows no trend related to the FIP. Our results differ from those of Peretz et al (2015) Peretz et al (2015) could be due to our better statistics, which allow us to use a 3-T model to fit the spectrum, thus with a better sampling of the region where oxygen lines are formed. Our result also contradicts the conclusion made by Wood & Linsky (2010), followed by Laming (2015), in which FIP-related effects in dwarfs are correlated with spectral type, using only stars with log L X (erg s −1 )< 29.…”
Section: ι Hor As a Young Solar Analogcontrasting
confidence: 80%
“…It has been proposed that activity cycles can also act as weather seasons for biological processes in exoplanets under some circumstances (Mullan & Bais 2018). Peretz et al (2015) used the EPIC-pn spectrum to measure the coronal abundances of a few elements in ι Hor, which were then compared with the photospheric values in the literature. Our superb RGS combined spectrum allows for a more accurate measurement of the coronal abundances (Table 2, Fig.…”
Section: ι Hor As a Young Solar Analogmentioning
confidence: 99%
“…This discrepancy was previously noted by Maggio et al (2011) and Peretz et al (2015) based on an XMM spectrum from 2003 June 24, though those authors were looking for evidence of changes in coronal abundance behavior induced by high photospheric metallicity, rather than changes that might be induced by τ Boo A's exoplanet. One advantage of the Chandra spectrum analyzed here is that the τ Boo AB binary is resolved by Chandra, unlike XMM, meaning our τ Boo A spectrum is uncontaminated by any emission from the M2 V companion τ Boo B.…”
Section: Exoplanet Effects On Coronal Abundancesmentioning
confidence: 78%
“…Wood et al (2018) extended the FIP biasspectral type relationship to include stars of earlier spectral types A and F. It is worth noting that the observed composition of stellar coronae can be more complex than having either a straightforward FIP or IFIP effect. For example, Peretz et al (2015) found that all elements were consistently depleted in the coronae of six main sequence stars of spectral type F7-K1 compared to their respective photospheres, whether compared to solar abundances or the individual stellar abundances.…”
Section: Introductionmentioning
confidence: 99%